Biomaterial coated magnetically suspended axial flow blood pump - Jin, Gengzhou (2008)
A novel magnetically suspended blood pump is designed to meet the needs of long-term biocompatibility and reliability. The main feature of this pump is that its rotor is supported both passive and active magnet bearings. The active magnetic bearings are controlled by electronics circuit, and self-sensing technique provides a better reliability and sensing accuracy,